Law no. 76/2017 amending some provisions of the income tax law no. 91 of the year 2005, and stamp duty law no. 111 of the year 1980 = قرار رئيس جمهورية مصر العربية بالقانون رقم 76 لسنة 2017 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 وقانون ضريبة الدمغة الصادر بالقانون رقم 111 لسنة 1980 - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
law no. 76/2017 amending some provisions of the income tax law no. 91 of the year 2005, and stamp duty law no. 111 of the year 1980 قرار رئيس جمهورية مصر العربية بالقانون رقم 76 لسنة 2017 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 وقانون ضريبة الدمغة الصادر بالقانون رقم 111 لسنة 1980